The Emergence and Persistence of Candida auris in Western New York With No Epidemiologic Links: A Failure of Stewardship?. (6th March 2023) - McGann, Patrick; Lebreton, Francois; Aggarwal, Abhimanyu; Stam, Jason; Maybank, Rosslyn; Ficinski, Matthew; Bronstein, Melissa; Bennett, Jason W; Lesho, Emil
Abstract: Reports of Candida auris infection in patients without epidemiologic links to prior outbreaks are scarce. We describe the genomic epidemiology of such a case in Western New York. Before emergence, the patient received >60 days of excess antibiotics. Candida auris was recovered on near-patient surfaces after enhanced terminal cleanings.